The Effectiveness of Video Visual Scene Display-Assisted Behavioral Skills Training in the Instruction of Skills to Prevent Online Sexual Abuse Among Adults with Autism Spectrum Disorder. - Oğur, Çimen; Olçay, Seray (Archives of Sexual Behavior, 2025)
The present study aimed to determine the effectiveness of the video visual scene display-assisted behavioral skills training in skills to prevent online sexual abuse among adults with autism spectrum disorder (ASD). The study was conducted with three 21–23-year-old male individuals with ASD, and the multiple probe model across participants, a single-subject research model. The study findings demonstrated that all individuals acquired the skills to prevent online sexual abuse, generalized the acquired skills to different individuals, and maintained these skills for 2–4 weeks after the instruction. Furthermore, social validity data were collected from the participants, their parents, and teachers with the subjective analysis approach, and it was observed that participants, their parents, and teachers reported positive views about the instruction of the skills, the intervention, and the outcomes.